Bio-Guided Fractionation of Papaya Leaf Juice for Delineating the Components Responsible for the Selective Anti-proliferative Effects on Prostate Cancer Cells - Pandey, Saurabh; Walpole, Carina; Shaw, Paul N.; Cabot, Peter J.; Hewavitharana, Amitha K.; Batra, Jyotsna (Frontiers in Pharmacology, 2018)
Alternative therapies against cancer cells with minimal or no effect on healthy tissues are highly sought after. Prostate cancer (PCa) is the second most frequently diagnosed malignancy in males. The Carica papaya L. leaf extract has been traditionally used by Australian Aboriginal people for it’s anticancer properties. In this study, medium polar fraction of Papaya leaf extract that had shown anti-proliferative activity in prostate cancer cell lines in vitro, in earlier studies, was further fractionated to 28 fractions by semi-preparative HPLC. Nine of these fractions were identified to possess selective anti-proliferative responses on PCa cells in comparison to noncancerous cells of prostate gland origin. When these nine sub-fractions were mixed in various combinations, a combination containing six of the specific fractions (FC-3) showed the best potency. FC3 inhibited the growth of BPH-1, PC-3 and LNCaP cells in a concentration-dependent manner with an IC50 value < 20 µg/mL, while (unlike paclitaxel, the positive control) minimal effect was observed on the proliferation of noncancerous, WPMY-1 and RWPE-1cells. Furthermore, synergistic interaction of FC-3 with paclitaxel was observed with combination index values in the range of 0.89 – 0.98 and 0.85-1.10 on PC-3 and LNCaP cells, respectively. Untargeted qualitative analysis using UHPLC (Ultra High-Performance Liquid Chromatography)-QToF (Quadrupole Time of-Flight) mass spectrometry and screening against the METLIN database indicated presence of multiple known anticancer compounds in the FC-3 extract. These outcomes show that the potent and selective anti-proliferative effects are due to a range of bio-active compounds within the medium polar fraction of papaya leaf juice.